Temporal dynamics of soil moisture and rainfall erosivity in a tropical volcanic archipelago - de Assunção Montenegro, Abelardo Antônio; dos Santos Souza, Thais Emanuelle Monteiro; de Souza, Edivan Rodrigues; Montenegro, Suzana Maria Gico Lima (Journal of hydrology (Amsterdam), 2018)
•This paper addresses soil water dynamics and rainfall pattern in Fernando de Noronha.•It is the only oceanic island of Brazil continuously inhabited since over 500 years.•Soil moisture is strongly related to rainfall temporal pattern, from original data set.•The rainfall erosivity in the archipelago was identified as moderate to strong. Soil water availability has a strong role on vegetation conservation and biodiversity, particularly at vulnerable environments such as archipelagos, subject to significant temporal changes of climate and rainfall, which influence soil weathering and erosion processes. Few field studies on hydrology of volcanic islands in the Atlantic Ocean have been developed focusing on soil and water temporal dynamics and conservation, mainly because such studies require data with high temporal resolution, and also due to the financial costs involved with field data acquisition at such remote places. Considering the importance of soil moisture content to several hydrological processes and islands environmental sustainability, this study aimed to investigate the soil water temporal dynamics in relation to different rainfall patterns and also the rainfall erosivity and its temporal variation, and the resulting infiltration depths, during a typical hydrological period, in an experimental plot at the main watershed of Fernando de Noronha, in the Brazilian Atlantic Coast. Rainfall was recorded every 5 min, and soil moisture was intensely monitored by 16 moisture probes, installed at 10–40 cm and 40–70 cm layers, during three years, representing the typical local hydrological regime and seasons. Rainfall bursts pattern were identified and described. Experimental data allowed a hydrological model to be calibrated and validated, providing estimates of infiltration depths, which can be valuable for water resources planning and management. Hydrological patterns were determined for each erosive rainfall, depending on the precipitation peak position, as advanced, intermediate and delayed. The soil water effectiveness was also evaluated and related to the different rainfall patterns. Soil moisture is highest from April to June, close to saturation; whilst for the other months the values were close to the residual value. The rainfall erosivity in the archipelago was identified as moderate to strong, and the most frequent rainfall pattern was the advanced. Fast wetting-drying cycles during the rainfall events were observed, due to rainfall intermittency, evapotranspiration, and to soil hydraulic conductivity. It was observed the prevalence of high moisture indexes, with percentages higher than 40% (extremely effective level) for both investigated depths within the first 70 cm of soil, essential for plant water uptake. The observed rainfall erosivity highlights the importance of defining local strategies for soil and water conservation aimed at water security in the island. Based on a simulation model, which was successfully calibrated (Nash-Sutcliffe Efficiency Index NS = 0.76) and validated (NS = 0.81) for periods in the wet season, high infiltration depths have been identified, which contributes to canopy conservation in the archipelago.